Pemetaan Pola Perjalanan Wisata di Desa Lantan Kabupaten Lombok Tengah - Defita Stefania Ili; Anas Pattaray; Isdar Wahim (IAI Nasional Laa Roiba Bogor, 2024)
Increasing economic progress and prosperity have made tourism part of human needs and lifestyle. Currently, tourism is able to move interrelated economic chains and become a service industry that makes an important contribution to the world economy, thereby increasing economic welfare at the local community level, especially in tourist destination areas. Lantan Village is one of the 99 tourist villages that will be developed by the NTB provincial government, especially the Central Lombok district government. Lantan Village is located in North Batukeliang subdistrict, Central Lombok Regency, West Nusa Tenggara Province. Until now, Lantan Village does not have a maximum tourism travel pattern that involves all the tourist attractions in Lantan Village. This research uses a descriptive qualitative method. The data obtained was based on interviews with village officials, pokdarwis, local communities and tourists. This research produces recommendations for tourist travel patterns based on tourist attractions, facilities and infrastructure, accessibility, distance and travel time in Lantan village.